Tempoyak as a Biotechnology Learning Media: Innovation of Ethnoscience-Based PjBL E-module to Improve Science Literacy and Creativity of Phase E Students - Herlinawati, Nabila; Octavia, Bernadetta (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2025)
This research is motivated by the limitations of teaching materials that are less interactive and innovative and the low scientific literacy and creativity of students. The purpose of this study is to develop an ethnoscience-based Project-Based Learning (PjBL) e-module in making Tempoyak as a biotechnology teaching material to improve scientific literacy and creativity of Phase E students. The method used is Research and Development (R&D) with a 4D development model (Define, Design, Develop, and Disseminate). The research sample consisted of two classes, namely the experimental class using the ethnoscience-based PjBL e-module and the control class using conventional teaching materials. The effectiveness of the e-module was measured by comparing the results of the pretest and posttest, as well as the creativity questionnaire. The results showed that the developed e-module was effective in improving the scientific literacy and creativity of students. The average posttest score of the experimental class increased significantly compared to the control class. Thus, this e-module can be an alternative innovative teaching material that integrates science with local culture, which can improve scientific literacy and creativity.